Urban Infestation Patterns of Argentine Ants, Linepithema humile, in Los Angeles. (16th July 2012) - Gilboa, Smadar; Klotz, John H.; Nonacs, Peter
Abstract : Infestations of buildings by Argentine ants, Linepithema humile (Mayr), were monitored on the campus of the University of California, Los Angeles. Foraging ant activity peaked during the hotter months of the year. The mean monthly maximum temperature, but not rainfall, positively correlated with indoor infestation frequency. Neither garden size nor the predominant groundcover vegetation correlated with the number of foraging ants at baits within gardens. Although the number of foraging ants outside a building varied over 40-fold, ant density in gardens did not predict the likelihood of infestation within the building. Also, the type of vegetative groundcover employed did not predict infestation frequency. There was, however, a significant negative relationship between the size of the garden outside of a building and the number of infestations. Given the large foraging area of L. humile workers, buildings next to small gardens may be infested simply because they lie within the "normal" foraging area of a colony. The best predictor of which rooms were infested within buildings was the presence of a water source. Thus providing water for ant colonies outside and away from buildings may be one method of integrated pest management to reduce the proclivity of ants to infest structures.